Bacterial Effector-Involved Temporal and Spatial Regulation by Hijack of the Host Ubiquitin Pathway - Kubori, Tomoko; Nagai, Hiroki (Frontiers in Microbiology, 2011)
Ubiquitination is one of the most conserved post-translational modifications of proteins, and is involved in essential eukaryotic cellular processes. These include protein degradation, transcriptional regulation, cell-cycle progression, and signaling. Microbial pathogens have evolved sophisticated systems to hijack host cellular functions for their own benefit. Central to these systems are protein transport machineries; many pathogenic bacteria inject “effector proteins” to modulate host cellular processes including the ubiquitin pathway. Numerous bacterial pathogens have been found to modulate the host ubiquitin system in various ways. In this review, we focus on three examples of temporal and spatial regulation of bacterial effectors, which are mediated by the host ubiquitin system. Subversion of the host ubiquitin system must be a widespread strategy among pathogenic bacteria to accomplish successful infection.